Masalah Penegakan Hukum Bandar Judi Online : Perspektif KUHP Baru Dan Hukum Islam - Rosyid Zain Achmadi; Suciyani (Cattleya Darmaya Fortuna, 2026)
The rise of online gambling practices (judol) in Indonesia poses a serious challenge for law enforcement, as existing normative instruments have not fully anticipated the digital tranformation and transnational nature of such crimes. This study examines the probhlems of law enforcement against organizers or operators of online gambling through two normative frameworks: Article 426 of Law Number 1 of 2023 concerning the new criminal code (New Penal Code) and the perspective of Islamic law. Using a doctrinal legal research method, this study positions law as a written gap, an imbalance in enforcement practices that predominantly target low level offenders, regulatory disharmony, and the lack of focused crminal liability on operators as the primary actors. The perpective islamic law emphasizes the importance of imposing punishment on those who control the system and gain the greates benefit. This study recommends a reorientation of law enforcement towars substantive justice and community protection.